The role of height-associated loci identified in genome wide association studies in the determination of pediatric stature - Frackelton Edward C; Deliard Sandra; Garris Maria L; Thomas Kelly A; Keating Brendan J; Hou Cuiping; Glessner Joseph T; Kim Cecilia E; Sleiman Patrick M; Wang Kai; Mentch Frank D; Zhang Haitao; et al. (BMC, 2010)
Abstract Background Human height is considered highly heritable and correlated with certain disorders, such as type 2 diabetes and cancer. Despite environmental influences, genetic factors are known to play an important role in stature determination. A number of genetic determinants of adult height have already been established through genome wide association studies. Methods To examine 51 single nucleotide polymorphisms (SNPs) corresponding to the 46 previously reported genomic loci for height in 8,184 European American children with height measurements. We leveraged genotyping data from our ongoing GWA study of height variation in children in order to query the 51 SNPs in this pediatric cohort. Results Sixteen of these SNPs yielded at least nominally significant association to height, representing fifteen different loci including EFEMP1-PNPT1, GPR126, C6orf173, SPAG17, Histone class 1, HLA class III and GDF5-UQCC. Other loci revealed no evidence for association, including HMGA1 and HMGA2. For the 16 associated variants, the genotype score explained 1.64% of the total variation for height z-score. Conclusion Among 46 loci that have been reported to associate with adult height to date, at least 15 also contribute to the determination of height in childhood.